Network pharmacology integrated with molecular docking and experimental validation elucidates the therapeutic potential of Forsythiae Fructus extract against hepatitis B virus-related hepatocellular carcinoma - Chen, Fuqing; Cai, Yifan; Chen, Changzhou; Zhou, Jianyin (Frontiers in Oncology, 2025)
BackgroundForsythiae Fructus (FF), a widely used traditional Chinese medicine, possesses anti-inflammatory, antiviral, and anticancer properties. However, the precise anticancer mechanisms of FF against hepatitis B virus (HBV)-related hepatocellular carcinoma (HCC) remain poorly understood. This study therefore aims to investigate the therapeutic potential of FF in HBV-related HCC and elucidate its underlying mechanisms.MethodsThe active components of FF and their putative target proteins were identified through network pharmacology, and their interactions were further validated via molecular docking and molecular dynamics (MD) simulations. In vitro assays were performed to evaluate the effects of FF extract on the viability, proliferation, and apoptosis of HBV-related HCC (HepG2.2.15) cells, along with the underlying molecular mechanisms. In vivo studies were performed to investigate the inhibitory effects of FF extract on subcutaneous xenograft tumors in nude mice, quantify serum cytokine levels, and evaluate the expression of key target proteins by immunohistochemistry.ResultsA total of 23 active components of FF and their 201 associated targets were identified using the TCMSP database, whereas 1,296 differentially expressed genes related to HBV-related HCC were retrieved from the GEO database. We identified 42 overlapping target genes between FF and HBV-related HCC. KEGG pathway analysis revealed the IL-17 signaling pathway as a pivotal pathway, with three core genes (c-Jun, ESR1, and MMP9) demonstrating prognostic significance in survival outcomes. Ten compounds were classified as high-quality candidates. Molecular docking studies demonstrated that Bicuculline exhibited the strongest binding affinity toward the core target genes, while MD simulations confirmed the stability of Bicuculline-JUN/ESR1/MMP9 complexes. In vitro experiments demonstrated that FF extract significantly inhibited the viability and proliferation of HepG2.2.15 cells, induced apoptosis, and exerted its effects via modulation of the IL-17/MAPK signaling pathway. Notably, adenovirus-mediated overexpression experiments showed that ESR1 enhanced FF’s anti-HCC effects, whereas JUN and MMP9 partially counteracted them, confirming their roles as functional targets. In vivo studies further confirmed that FF suppressed tumor growth, reduced serum levels of ALT, AST, TNF-α, and IL-17B in mice, and modulated the expression of core target genes.ConclusionsThe therapeutic potential of FF in HBV-related HCC was demonstrated, with its mechanism likely involving the regulation of multiple components, targets, and pathways. These findings establish a solid scientific foundation for exploring FF as a therapeutic option for HBV-related HCC.